2021
DOI: 10.1021/acs.accounts.0c00819
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Synthesis and Reactivity of Transition Metal σ-Borane/Borate Complexes

Abstract: Conspectus The coordination of an element–element σ bond to a transition metal (TM) is both a fundamentally intriguing binding mode and of critical importance to metal-mediated bond activation mechanisms and catalysis, particularly the hotly contested field of C–H activation. TM σ complexes of dihydrogen (i.e., H–H) and silanes (H–SiR3) have been extensively studied, the latter being of interest as models for the (generally unstable and unisolable) σ complexes of alkanes (i.e., H–CR3). TM σ complexes of hydrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 78 publications
0
18
0
Order By: Relevance
“…Surprisingly, only one dihydridoborate unit participates in the reaction, other one probably provided ancillary support to the metal centre. The C=C and B−C bond distances of 1.386(4) and 1.548(4) Å in 10 b respectively, are analogous to those of η 4 ‐HBCC‐coordinated ruthenium complexes [4b] . The Ru1‐B1 bond distance of 2.353(3) Å is significantly elongated upon coordination with alkene as compared to uncoordinated one (Ru1‐B2 2.143(3) Å).…”
Section: Figurementioning
confidence: 78%
“…Surprisingly, only one dihydridoborate unit participates in the reaction, other one probably provided ancillary support to the metal centre. The C=C and B−C bond distances of 1.386(4) and 1.548(4) Å in 10 b respectively, are analogous to those of η 4 ‐HBCC‐coordinated ruthenium complexes [4b] . The Ru1‐B1 bond distance of 2.353(3) Å is significantly elongated upon coordination with alkene as compared to uncoordinated one (Ru1‐B2 2.143(3) Å).…”
Section: Figurementioning
confidence: 78%
“…To investigate the chelation mode of ZnI 2 with Int-III, a variety of possible complexes with different chelation modes were extensively screened. The results revealed that the most favored chelation mode contains a ZnI 2 -chelated six-membered ring, where ZnI 2 coordinates with both the carbonyl oxygen atom and the B-H bond 58,59 (Int-III-B-1 in Fig. 7a).…”
Section: H Bnmentioning
confidence: 99%
“…As listed in Table 1, the Ru-B distance of 2.172(4) Å for trans-4 is consistent with that of bis(dihyroborate) complex, Ru[(μ-H) 2 BC 8 H 14 ] 2 (PCy 3 ) 29 (2.160(2) Å) and other reported dihyroborate species. [29][30][31][32][33] The Ru-B distances in trans-4 fall in the range of2.103(2)-2.266(8) Å, 15 which are significantly longer as compared to those of σ-borane complexes, for example, [Ru(PCy 3 ) 2 (H) 2 (BH 2 Mes)] 29b (1.938(4) Å) and [Cp*Ru(P i Pr 3 )(BH 2 Mes)]B(C 6 F 5 ) 4 34 (1.921(2) Å). The B1-Ru1-B1 angle of 180.0(2)° shows a perfect symmetrical coordination of borane to metal center, unlike tetrahydroborate species, 2 Ru(η 2 -BH 4 )] 32 (177.4(4)°) and Ru[(μ-H) 2 BC 8 H 14 ] 2 (PCy 3 ) 30 (147.68(8)°).…”
Section: Chemical Science Accepted Manuscriptmentioning
confidence: 99%
“…As part of our current interest in activation of boranes utilizing cooperative reactivity, 15 we have synthesized a number of molybdenum( ii ) hydroborate species, in which BH 3 is stabilized through Mo–H–B(H 2 )–E molybdacycles (E = S, Se or Te). 16 Further, very recently, we have established cooperative Si–H and B–H bond activations by a κ 2 - N , S -chelated borate complex, trans – mer -1b that led to the formation of six-membered ruthenahetero-cycles through hemilabile ring-opening of Ru–N bonds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation